Association between attendance at a behavioral change communication module and dysmenorrhea prevalence among female university students: A propensity score matched comparative study - Liton Chandra Sen; Md Jamal Uddin; Ishrat Jahan; Nadia Salekin; Jahid Hasan Shourove; Md Mosiur Rahman; Cuilin Zhang; Davidson H. Hamer; GM Rabiul Islam (PLoS ONE, 2026)
Background Dysmenorrhea is the most common menstrual disorder among young women and often disrupts daily activities and well-being. Although pharmacological management is widely used, sustainable non-pharmacological strategies remain underexplored, particularly in low-resource settings. This study assessed the association between a behavioral change communication (BCC) module and dysmenorrhea among female university students in Bangladesh. Methods A matched cross-sectional comparative study initially recruited 498 female students from three public universities. Students attending three BCC sessions were classified as exposed group, while those who did not attend served as non-exposed group. After exclusions, 472 participants were analyzed. Propensity score matching (1:1 nearest-neighbor, caliper of 0.01 and no replacement) yielded 98 matched pairs. The primary measure was the average treatment effect on the treated (ATT), estimated using a doubly robust method to evaluate the association between BCC exposure and dysmenorrhea prevalence in the matched samples. Results In matched samples, the overall prevalence of dysmenorrhea was 69.4%. Prevalence was higher among non-exposed participants (77.6%) compared with those exposed to the BCC module (61.2%). Using the doubly robust estimator, BCC-exposed participants had a 23 percentage-point lower prevalence of dysmenorrhea than non-exposed participants (ATT = −0.23; 95% CI: −0.33 to −0.13; p < 0.001), after adjustment for observed covariates. This association remained consistent and statistically significant across regression adjustment and inverse probability weighting estimators of the ATT. Participants exposed to BCC module more frequently reported regular physical activity and higher dietary diversity, both associated with lower odds of dysmenorrhea in post-matching analyses. Conclusion Exposure to a theory-driven BCC module was associated with lower reported dysmenorrhea prevalence and healthier lifestyle behaviors among female university students in Bangladesh. Due to non-random design and lack of baseline outcome data, results are associative rather than causal, highlighting the need for further longitudinal or randomized studies to evaluate the impact of BCC programs.